PERANCANGAN VISUAL IDENTITY JERUK SIAM GUNUANG OMEH KELOMPOK TANI FAJAR HARAPAN - RAHMAITI ARNIA SUKMA, Dr. Syafwndi, M.Sn., Drs. Ariusmedi. M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of this article is to design the Visual Identity of Gunuang Omega, Siamese oranges, in order to provide a visual identity and identity for Siamese oranges from the Fajar Harapan farmer group, which will function later as (1) Designing a logo to display identity, from